Beispiel Nr: 26
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -2x^3+12x^2-18x =0\\ \\ \textbf{Rechnung:} \\ x(-2x^2+12x-18)=0 \Rightarrow x=0 \quad \vee \quad-2x^2+12x-18=0\\ \\ -2x^{2}+12x-18 =0 \\ x_{1/2}=\displaystyle\frac{-12 \pm\sqrt{12^{2}-4\cdot \left(-2\right) \cdot \left(-18\right)}}{2\cdot\left(-2\right)} \\ x_{1/2}=\displaystyle \frac{-12 \pm\sqrt{0}}{-4} \\ x_{1/2}=\displaystyle \frac{-12 \pm0}{-4} \\ x_{1}=\displaystyle \frac{-12 +0}{-4} \qquad x_{2}=\displaystyle \frac{-12 -0}{-4} \\ x_{1}=3 \qquad x_{2}=3 \\ \underline{x_1=0; \quad1\text{-fache Nullstelle}} \\\underline{x_2=3; \quad2\text{-fache Nullstelle}} \\$